Kepemimpinan Nusantara: Integrasi Nilai Lokal dalam Praktik Kepemimpinan Kontemporer - Subakdi Subakdi (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
This study aims to explore and examine the leadership model based on local values ​​that have developed in various regions of the archipelago, as well as its relevance in contemporary leadership practices. Indonesia as a country with high cultural diversity holds many traditional leadership value legacies, such as deliberation, mutual cooperation, and the principle of balance between individual and collective interests. Through a qualitative-descriptive approach, this study analyzes various traditional leadership practices from several regions such as Java, Bali, Minangkabau, and Bugis-Makassar, then identifies the main elements that can be integrated into modern leadership styles in both the public and private sectors. The results of the study indicate that local values ​​not only enrich existing leadership models, but are also able to strengthen the legitimacy, ethics, and effectiveness of leadership in an increasingly complex social context. This study recommends the development of a hybrid leadership model that combines local wisdom with global demands, as an adaptive solution in facing the dynamics of changing times.